Brucella abortus Rough-Type Mutant Induces Ferroptosis and More Oxidative Stress in Infected Macrophages - Hai Hu; Guangdong Zhang; Mingxing Tian; Xiang Guan; Yi Yin; Chan Ding; Shengqing Yu (Pathogens, 2023)
Brucella is an intracellular parasitic bacterium that uses multiple strategies to evade the host’s defense mechanisms. However, how Brucella manipulates the host-induced oxidative stress and relevant biological processes are still poorly understood. In this study, a comparative transcriptome assay of macrophages infected with Brucella abortus S2308 and its rough mutant RB14 was performed to investigate the differentially expressed genes which might be associated with the pathogenic mechanism of Brucella. Our results showed that numerous host pro-oxidative and antioxidative stress genes were differentially expressed in macrophages infected with B. abortus S2308 and mutant RB14 at 4, 8, 24, and 48 h post-infection. Interestingly, we found that several ferroptosis-associated genes were differentially expressed during B. abortus RB14 infection. Moreover, we found that the rough mutant RB14-induced macrophage death was associated with reduced levels of host glutathione and glutathione peroxidase 4, together with increased free iron, lipid peroxidation, and ROS, all of which are important hallmarks of ferroptosis. The ferroptosis occurring during infection with RB14 was reduced by treatment with the inhibitor ferrostatin-1. However, B. abortus S2308 infection did not induce these hallmarks of ferroptosis. Taken together, our results demonstrate that ferroptosis is involved in rough B. abortus infection. Investigating how Brucella manipulates oxidative stress and ferroptosis in its host will be helpful to clarify the pathogenicity of B. abortus.